Pola Rektrumen Kementerian Agama dalam Menentukan TIM Petugas Haji Indonesia Kota Tanjungbalai - Alfikri Rozan Sinaga; Farhan Indra (Universitas Muhammadiyah Enrekang, 2023)
The Recruitment Pattern of the Ministry of Religion in Determining the Tanjungbalai City Indonesian Hajj Officer Team. This study aims to determine the Recruitment Patterns of the Ministry of Religion in Determining the Tanjungbalai City Indonesian Hajj Officer Team both from the recruitment process, recruitment requirements, recruitment sources, recruitment methods. This study uses a qualitative research method approach. Primary data was obtained directly through interviews, namely the Ministry of Religion of Tanjungbalai City. Secondary data obtained from research documents. The results of the study show that the recruitment pattern of the Ministry of Religion in determining the team of Indonesian haj officers in the city of Tanjungbalai began with the appointment of the Directorate General of the Ministry of Religion of the Republic of Indonesia, then a letter was sent to the Province and again to the city. Ministry of Religion. Then the sources are from internal and external although externally the city Ministry of Religion is only to participate so that only a few take part in the registration of haj officers, because the success of recruitment depends on the large number of those who register to become haj officer recruitment at the Ministry of Religion of Tanjungbalai City.